Wandering tales: evolutionary origins of mental time travel and language - Corballis, Michael C. (Frontiers in Psychology, 2013)
A central component of mind wandering is mental time travel, the calling to mind of remembered past events and of imagined future ones. Mental time travel may also be critical to the evolution of language, which enables us to communicate about the nonpresent, sharing memories, plans, and ideas. Mental time travel is indexed in humans by hippocampal activity, and studies also suggest that the hippocampus in rats is active when the animals replay or pre play activity in a spatial environment, such as a maze. Mental time travel may have ancient origins, contrary to the view that it is unique to humans. Since mental time travel is also thought to underlie language, these findings suggest that language evolved gradually from pre-existing cognitive capacities, contrary to the view of Chomsky and others that language and symbolic thought emerged abruptly, in a single step, within the past 100,000 years.